Effects of bridging plus exercises with heel lift on lower extremity muscles - Yoo, Won-gyu (J Phys Ther Sci, 2016)
[Purpose] This study investigated the effects of the bridging plus exercise with heel lift on lower extremity muscles. [Subjects and Methods] Nine healthy males participated. The subjects performed bridging exercises under two conditions. Surface electromyography was used to measure the electrical activities of the medial hamstring (MH) and the gluteus maximus (GM) muscles. [Results] Activation of the MH muscle during bridging with heel lift decreased, and activation of the GM muscle during bridging with heel lift increased compared to those with the bridging exercise. [Conclusion] This result showed that bridging plus exercises with heel lift could be an effective exercise for patients with compensatory mechanisms during bridging exercises, such as weak GM with hamstring tightness.